International Expert Opinions and Recommendations on the Use of Melatonin in the Treatment of Insomnia and Circadian Sleep Disturbances in Adult Neuropsychiatric Disorders - Palagini, Laura; Manni, Raffaele; Aguglia, Eugenio; Amore, Mario; Brugnoli, Roberto; Bioulac, Stéphanie; Bourgin, Patrice; Micoulaud Franchi, Jean-Arthur; Girardi, Paolo; Grassi, Luigi; Lopez, Régis; Mencacci, Claudio; et al. (Frontiers in Psychiatry, 2021)
Introduction. Insomnia and circadian rhythm disorders, such as the delayed sleep phase syndrome, are frequent in psychiatric disorders and their evaluation and management in early stages should be a priority. The aim of this paper was to express recommendations on the use of exogenous melatonin, which exhibits both chronobiotic and sleep-promoting actions, for the treatment of these sleep disturbances in psychiatric disorders. Methods To this aim, we conducted a systematic review according to PRISMA on the use of melatonin for the treatment of insomnia and circadian sleep disorders in neuropsychiatry. We expressed recommendations for the use of melatonin in psychiatric clinical practice for each disorder using the RAND/UCLA appropriateness method. Results We selected forty-one studies, which included mood disorders, schizophrenia, substance use disorders, attention deficit hyperactivity disorders, autism spectrum disorders, neurocognitive disorders and delirium; no studies were found for both anxiety and eating disorders. Conclusion The administration of prolonged release melatonin at 2-10 mg, 1-2 hours before bedtime, might be used in the treatment of insomnia symptoms or comorbid insomnia in mood disorders, schizophrenia, in adults with autism spectrum disorders, neurocognitive disorders and during sedative-hypnotics discontinuation. Immediate release melatonin at <1mg might be useful in the treatment of circadian sleep disturbances of neuropsychiatric disorders.